Effects of metro transit on the ownership of mobility instruments in Xi'an, China. (May 2017) - Huang, Xiaoyan; Cao, Xinyu (Jason); Yin, Jiangbin; Cao, Xiaoshu
Highlights: The effects of metro transit on the ownership of autos, bikes, ebikes, and motorcycles were examined. Both cross-sectional and quasi-longitudinal analyses were employed. Metro transit has a positive association with bike ownership. Metro transit has the potential to slow the growth of autos and ebikes. Abstract: Most studies regarding the effects of rail transit on auto ownership have yet to disentangle the influences of the built environment surrounding stations and residential self-selection from the impact of rail transit itself. There is also limited knowledge on the effects of rail investments in developing countries on ownership of mobility instruments, which has recently proliferated because of economic growth. Using the 2014 data from Xi'an, this study explores the joint influences of metro transit on the ownership of autos, bikes, ebikes, and motorcycles. The cross-sectional analysis shows that metro is negatively associated with auto ownership and ebike ownership whereas it has a positive association with bike ownership. The quasi-longitudinal analysis indicates that moving into metro neighborhoods is negatively associated with the changes of auto and ebike ownerships. These results suggest that metro development helps curb the growth of autos and fight against the negative consequences of ebikes, and has the potential to achieve sustainable travel.